2019
DOI: 10.1177/2040622319891587
|View full text |Cite|
|
Sign up to set email alerts
|

Addressing cost and time barriers in chronic disease management through telemedicine: an exploratory research in select low- and middle-income countries

Abstract: Background: Despite evidence supporting telehealth provision in developed countries, there is limited evidence regarding its economic benefits for patients living in areas where access and cost present major barriers to health care, particularly in low- and middle-income countries (LMICs). This study explores the economic benefits of telemedicine for patients, in terms of cost and times savings, and its potential role in improving chronic disease outcomes. Methods: This retrospective cross-sectional study comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
55
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(59 citation statements)
references
References 16 publications
2
55
0
2
Order By: Relevance
“…Temporary government funding will be necessary to roll out telemedicine to both rural and urban settings, as well as relaxations to legislation that allow practitioner reimbursement of telemedicine services (101). A study by Sayani et al, addressing the cost and time barriers in chronic disease management through telemedicine in LMICs, found telemedicine to be economically beneficial not only by reducing the socioeconomic barriers to cost and access but also by increasing the uptake of services (102). Another systematic review of studies conducted on costs of home-based telemedicine programs from 2000 to 2017 found that home telemedicine programs reduced care costs, although detailed cost data were either incomplete or not presented in detail (103).…”
Section: Cost-benefit Analysismentioning
confidence: 99%
“…Temporary government funding will be necessary to roll out telemedicine to both rural and urban settings, as well as relaxations to legislation that allow practitioner reimbursement of telemedicine services (101). A study by Sayani et al, addressing the cost and time barriers in chronic disease management through telemedicine in LMICs, found telemedicine to be economically beneficial not only by reducing the socioeconomic barriers to cost and access but also by increasing the uptake of services (102). Another systematic review of studies conducted on costs of home-based telemedicine programs from 2000 to 2017 found that home telemedicine programs reduced care costs, although detailed cost data were either incomplete or not presented in detail (103).…”
Section: Cost-benefit Analysismentioning
confidence: 99%
“…In addition to these benefits, telemedicine can provide considerable economic benefits. 37 Data from 25 182 teleconsultation visits suggest that a total of US$9 175 132, and 1 876 146 hours (213.1 years) in chronic disease management have been saved with the use of telemedicine in low-income and middle-income countries.…”
Section: Discussionmentioning
confidence: 99%
“…It includes the availability of open information on the health, treatment, complications, and biomedical research in the Internet. On the other hand, the diagnostic and medical consulting services are becoming more accessible and available even in low-income countries [2,3]. Telemedicine provides an opportunity for people from rural and remote regions to get high-quality consulting and advice, while online pharmacy platforms allow obtaining the necessary drugs without unnecessary commuting [4,5].…”
Section: Introductionmentioning
confidence: 99%